2017
DOI: 10.1039/c6nr05886h
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric sensing of nucleic acids using chemically modified nanopores

Abstract: Unlike the overwhelming majority of nanopore sensors that are based on the measurement of a transpore ionic current, here we introduce a potentiometric sensing scheme and demonstrate its application for the selective detection of nucleic acids. The sensing concept uses the charge inversion that occurs in the sensing zone of a nanopore upon binding of negatively charged microRNA strands to positively charged peptide-nucleic acid (PNA) modified nanopores. The initial anionic permselectivity of PNA-modified nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The study revealed that DNA probes microspotted in both single stranded and prehybridized form can ultimately provide the same hybridization efficiency. For high spot density DNA microarrays the prehybridization with a complementary strand may not be practical due to higher cost, but it contours as the most robust approach for (i) kinetic measurements, (ii) small spot density DNA microarrays and (iii) in case of surface morphologies or nanoscale confinements where reproducible hybridization efficiencies are otherwise difficult to achieve, e.g., nanopores [35]. Arrays with microspotted ssDNA strands require more elaborate optimization in terms of hybridization efficiency, however allows for fine tuning of the surface coverage for a better discrimination of single mismatch targets.…”
Section: Effect Of the Probe Surface Density On Kinetic Measurements mentioning
confidence: 99%
“…The study revealed that DNA probes microspotted in both single stranded and prehybridized form can ultimately provide the same hybridization efficiency. For high spot density DNA microarrays the prehybridization with a complementary strand may not be practical due to higher cost, but it contours as the most robust approach for (i) kinetic measurements, (ii) small spot density DNA microarrays and (iii) in case of surface morphologies or nanoscale confinements where reproducible hybridization efficiencies are otherwise difficult to achieve, e.g., nanopores [35]. Arrays with microspotted ssDNA strands require more elaborate optimization in terms of hybridization efficiency, however allows for fine tuning of the surface coverage for a better discrimination of single mismatch targets.…”
Section: Effect Of the Probe Surface Density On Kinetic Measurements mentioning
confidence: 99%
“…In presence of the target miR, DNA displacement occurs accompanied by the release of the AuNPs, thus affording a measurable variation of system impedance. Based on the obtained results, the same group later reported on a new, optimized, nanopore array for potentiometric detection of the same miR, exploiting a different approach [69]. In this device, gold nanopores were decorated with positively charged PNAs to ensure anionic permselectivity, thus avoiding the passage of cations through the pore.…”
Section: Nanopore-based Methodologiesmentioning
confidence: 99%
“…Furthermore, the potentiometric transduction mechanism could be also extended for the selective detection of nucleic acids with peptide nucleic acid functionalized nanopores. [14]…”
Section: Chemically Modified Nanoporesmentioning
confidence: 99%